2013
DOI: 10.1002/col.21804
|View full text |Cite
|
Sign up to set email alerts
|

Perceived sexual receptivity and fashionableness: Separate paths linking red and black to perceived attractiveness

Abstract: Previous research has documented that the colors red and black influence perceptions of attractiveness for men viewing women. Perceived sexual receptivity has been identified as a mediator for the red-attraction link, but there has been no research to date on the mechanism linking black to attractiveness. We conducted an experiment to test whether separate, unique mediators were responsible for color effects on attractiveness. We hypothesized that red would lead to attractiveness via perceived sexual receptivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 37 publications
4
51
2
Order By: Relevance
“…Recent research has shown that heterosexual men are more likely to rate a woman as more attractive when she is displaying red (e.g., when surrounded by red, holding something red, or wearing red clothing or lipstick; Elliot & Niesta, 2008;Gilston & Privitera, 2016;Guéguen, 2012aGuéguen, , 2012bGuéguen & Jacob, 2012a, 2012bLin, 2014;Pazda, Elliot, & Greitemeyer, 2014;Robert, Havilcek, & Owen, 2010;Stephen & McKeegan, 2010;Young, 2015). These findings are presumably due, in part, to a pervasive link between red and romance across time and cultures.…”
Section: Facial Redness Increases Men's Perceived Healthiness and Attmentioning
confidence: 99%
“…Recent research has shown that heterosexual men are more likely to rate a woman as more attractive when she is displaying red (e.g., when surrounded by red, holding something red, or wearing red clothing or lipstick; Elliot & Niesta, 2008;Gilston & Privitera, 2016;Guéguen, 2012aGuéguen, , 2012bGuéguen & Jacob, 2012a, 2012bLin, 2014;Pazda, Elliot, & Greitemeyer, 2014;Robert, Havilcek, & Owen, 2010;Stephen & McKeegan, 2010;Young, 2015). These findings are presumably due, in part, to a pervasive link between red and romance across time and cultures.…”
Section: Facial Redness Increases Men's Perceived Healthiness and Attmentioning
confidence: 99%
“…Several further experiments have corroborated the reasoning that there is a positive effect of red on attractiveness judgments, which is caused by sexual receptivity expectations (Elliot, Greitemeyer, & Pazda, ; Guéguen ; Niesta Kayser, Elliot, & Feltman, ; Pazda et al ; Young ). In accordance with these findings on red and the perceived attractiveness of others, we now propose that sexual receptivity also functions as mediator regarding the red effect on self‐attractiveness.…”
Section: Underlying Processes Of the Red Effect In The Affiliation Comentioning
confidence: 80%
“…In Experiment 3, we examined the processes underlying the self‐perception red effect. Previous findings demonstrated that male participants associated female targets wearing a red shirt with higher sexual receptivity resulting in higher attractiveness ratings (Pazda et al ; ; see also Guéguen, ). Regarding male targets, Elliot et al () showed that female participants perceived men with a red shirt as high in status and therefore rated these male targets as more attractive (see also Stephen et al, ).…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…Starting with a seminal paper on the "Red-Romance Hypothesis" (Elliot and Niesta 2008), a large body of literature has accumulated showing that, for instance, wearing a red T-shirt or being shown in front of a red background strongly enhances the attractiveness of men Buechner et al 2015) and women (Elliot and Niesta 2008;Kayser et al 2010;Elliot and Pazda 2012;Pazda et al 2012;Elliot et al 2013aElliot et al , 2013bElliot and Maier 2013;Pazda et al 2014a;Pazda et al 2014b). Some of these studies highlighted the parallels to the zebra finch example Elliot and Maier 2012).…”
mentioning
confidence: 99%